Pengaruh Penggunaan Sosial Media Dan Brand Equity Terhadap Keputusan Pembelian Pada Konsumen Umkm Lapak Sayur Pasar Paramount Gading Serpong - Abdiel Hazmi; Rissa Hanny (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the effect of social media usage and brand equity on consumers’ purchasing decisions at vegetable stall MSMEs in Pasar Modern Paramount Gading Serpong. The research focuses on examining the partial and simultaneous effects of these variables on purchasing decisions, considering the increasing competition among MSMEs and changes in consumer behavior in the digital era, This research employs a quantitative method with an associative approach. Data were collected through questionnaires distributed to consumers of vegetable stall MSMEs as research respondents. Data analysis techniques include validity tests, reliability tests, classical assumption tests, linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²), The results indicate that social media usage and brand equity partially have a positive and significant effect on purchasing decisions. Simultaneously, both variables also significantly influence consumers’ purchasing decisions. This study is expected to provide practical insights for MSME actors in developing effective marketing strategies through social media utilization and strengthening brand equity.